OCT angiography, RNFL and the visual field at different values of intraocular pressure - Kral, Jakub; Lestak, Jan; Nutterova, Elena (Biomedical reports, 2022)
The aim of the present study was to investigate the relationship between intraocular pressure (IOP), vessel density (VD), retinal nerve fiber layer (RNFL) parameters and overall defect (OD) of the visual field in eyes where antiglaucoma treatment had not yet been initiated. A total of 61 subjects (122 eyes) who had an IOP of >20 mmHg on several occasions, in at least one eye, in routine outpatient care were included. These were subjects who had never been treated for hypertension glaucoma. The cohort was divided into four subgroups. In the first group, there were 18 eyes with an IOP value of <20 mmHg. In the second group, there were 39 eyes with IOP values of 20-22 mmHg. The third group consisted of 32 eyes with IOP values of 22-24 mmHg and the final group consisted of 33 eyes with IOP values of >24 mmHg. The IOP results were compared with VD, RNFL and OD using Pearson's correlation coefficient to assess the relationship between the selected parameters. RNFL and OD were moderately correlated only in the group of eyes with an IOP value >24 (r=0.48); in the other groups the correlation was very weak. However, changes in visual field were already observed in eyes with IOP 20-22 mmHg (r=-0.27). There was a moderate correlation in eyes with an IOP value >24 mmHg (r=-0.53). The most significant result observed was the relationship between VD and RNFL. In eyes with an IOP value ≤20, a moderate to strong correlation between these parameters was observed. This relationship increased with increasing IOP values up to a very strong correlation in the group with an IOP value >24 mmHg. A moderate to strong dependence between VD and RNFL in eyes with an IOP value ≤20 mmHg was observed, and this dependence was very strongly correlated in the eyes with an IOP value >24 mmHg.
Keywords: Optical Coherence Tomography angiography; vessel density; retinal nerve fiber layer; overall defect of visual field; intraocular pressure